2017
DOI: 10.1111/jcmm.13196
|View full text |Cite
|
Sign up to set email alerts
|

C1q/TNF‐related protein 9 inhibits the cholesterol‐induced Vascular smooth muscle cell phenotype switch and cell dysfunction by activating AMP‐dependent kinase

Abstract: Vascular smooth muscle cells (VSMCs) switch to macrophage‐like cells after cholesterol loading, and this change may play an important role in the progression of atherosclerosis. C1q/TNF‐related protein 9 (CTRP9) is a recently discovered adipokine that has been shown to have beneficial effects on glucose metabolism and vascular function, particularly in regard to cardiovascular disease. The question of whether CTRP9 can protect VSMCs from cholesterol damage has not been addressed. In this study, the impact of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 50 publications
(58 reference statements)
2
32
0
Order By: Relevance
“…CTRP9 has been suggested to act as a regulator of vascular function, and to exert protective effects in ischemic diseases (12). The cytoprotective effects of CTRP9 have been well documented, through promoting cell proliferation, inhibiting the oxidative response, and modulating endoplasmic reticulum stress (13,33). The present study demonstrated that CTRP9 treatment promoted MSC proliferation and viability and increased their immunoregulatory and angiogenic abilities, accompanied by elongation of telomere length and recovery of telomerase activity.…”
Section: Discussionsupporting
confidence: 57%
“…CTRP9 has been suggested to act as a regulator of vascular function, and to exert protective effects in ischemic diseases (12). The cytoprotective effects of CTRP9 have been well documented, through promoting cell proliferation, inhibiting the oxidative response, and modulating endoplasmic reticulum stress (13,33). The present study demonstrated that CTRP9 treatment promoted MSC proliferation and viability and increased their immunoregulatory and angiogenic abilities, accompanied by elongation of telomere length and recovery of telomerase activity.…”
Section: Discussionsupporting
confidence: 57%
“…Simultaneously, we consider that cardiac CTRP9 expression might be regulated by PPAR-γ (Su et al, 2013), and CTRP9 prevents activation of the TLR4-MyD88-p65 pathway by activating AMPK to inhibit the cholesterol-induced vascular smooth muscle cell (VSMC) phenotype switch (Q. Liu et al, 2017). Conversely, we have known that the signaling molecules TLR4, AMPK, NF-κB, and PPAR-γ, which are associated with CTRP9, are involved in macrophage polarization.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, CTRP9 could inhibit NF‐κB activation and reduce expression of adhesion molecules (Jung et al, ). Finally, CTRP9 could protect the blood vessels through inhibiting cholesterol uptake in vascular smooth muscle cells (Liu, Zhang et al, ) and promoting cholesterol efflux to reduce the formation of foam cell in virtue of inducing autophagy in an AMPK/mTOR signaling pathway‐dependent manner (Zhang, Liu et al, ), particularly in that the high cholesterol level has been considered as a risk factor for vascular remodeling at present.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, another research showed that CTRP9 could reduce the levels of inflammatory cytokines in coronary atherosclerotic plaques in ApoE knockout mice, thereby increasing atherosclerotic plaque stability (Zhang et al, ). In addition, CTRP9 may enhance atherosclerotic plaque stability via inhibiting the phenotypic switch of vascular smooth muscle cells which are closely related to atherosclerotic plaque stability (Liu, Zhang et al, ).…”
Section: Introductionmentioning
confidence: 99%